Validation of the Daily Spiritual Experience Scale Short Forms among Russian Orthodox Christian women - Shankov, Fedor (Journal of religion and health, 2026)
Although widely used, the daily spiritual experience scale short form (S-DSES) has recently been criticized for conflating spiritual experiences with mental health outcomes, potentially obscuring true relationships between spirituality and health. This study evaluates the psychometric properties of three S-DSES versions in Russian Orthodox Christian women, addressing potential content-overlap concerns. A total of 1056 female participants primarily from Russia (92.9%), Belarus (4.5%), and Ukraine (2.5%) completed surveys at two time points (August 2023 and February 2024), with a subsample (n = 144) retested for reliability. Exploratory and confirmatory factor analyses supported a single-factor structure for all versions, which demonstrated strong internal consistency (Cronbach's alpha ranging from .80 to .87) and good test-retest reliability (intraclass correlation coefficients ranging from .75 to .81). The 7-item S-DSES demonstrated superior model fit compared to the original 6-item version. The 4-item theistic version, consisting of the items that reference God and show the least conceptual overlap with psychosocial constructs, retained significant, though weaker, correlations with mental health and well-being measures, indicating that the association between perceived divine closeness and psychological well-being persists beyond potential measurement overlap. The 7-item S-DSES exhibited the strongest psychometric properties and is recommended for comprehensive assessment of daily spiritual experiences in Russian Orthodox Christian women, whereas the 4-item theistic version offers a concise alternative for studies of health outcomes that require minimal overlap with psychosocial content.